Persepsi Masyarakat tentang Pelaksanaan Kebijakan Pemerintah tentang Pencegahan Corona Virus Disease 2019 di Kecamatan Tikala Kota Manado - Jeini Ester Nelwan; Ester Candrawati Musa (Universitas Sam Ratulangi, 2020)
Background: The government has set various policies in order to control the spread of Corona Virus Disease 2019 (Covid-19). However, these efforts have not run optimally so that people who violate health protocols are still found which have an impact on increasing cases of Covid-19. The purpose of this study is to describe the public's perception of the implementation of government policies regarding the prevention of Covid-19 in Tikala District, Manado City.. Methode: This study was an observational study with a cross sectional study design. This research was conducted in Tikala District, Manado City in August 2020. The subjects in this study were 100 family heads who met the inclusion criteria. The research variable is the public's perception of the implementation of government policies in an effort to prevent Covid-19. The research data were analyzed by univariate. Presentation of data is made in table and narrative form. Result: The results of this study indicate that as many as 10% of the public think that the government has implemented policies in an effort to prevent Covid 19. The policies with the lowest value are efforts to disseminate information to the public about Covid-19. In addition, government supervision of the use of masks, measuring body temperature and ownership of health documents from health institutions from the public is still around 11%. This indicates that the government's efforts are still not maximal in implementing policies on preventing Covid-19. Conclusion: The conclusion of this study is that the government has not implemented a policy to prevent Covid-19 properly, especially in socialization and supervision efforts. Therefore, massive socialization and supervision efforts must be made and carried out jointly by the government and all stakeholders in the region in order to reduce the rate of increase in Covid 19.